Strong Anharmonicity‐Induced Low Thermal Conductivity and High n‐type Mobility in the Topological Insulator Bi1.1Sb0.9Te2S. Issue 41 (2nd September 2022) - Pathak, Riddhimoy; Dutta, Prabir; Srivastava, Ashutosh; Rawat, Divya; Gopal, Radha Krishna; Singh, Abhishek K.; Soni, Ajay; Biswas, Kanishka
Abstract: Intrinsically low lattice thermal conductivity ( κ lat ) while maintaining the high carrier mobility ( μ ) is of the utmost importance for thermoelectrics. Topological insulators (TI) can possess high μ due to the metallic surface states. TIs with heavy constituents and layered structure can give rise to high anharmonicity and are expected to show low κ lat . Here, we demonstrate that Bi1.1 Sb0.9 Te2 S (BSTS), which is a 3D bulk TI, exhibits ultra‐low κ lat of 0.46 Wm −1  K −1 along with high μ of ≈401 cm 2  V −1  s −1 . Sound velocity measurements and theoretical calculations suggest that chemical bonding hierarchy and high anharmonicity play a crucial role behind such ultra‐low κ lat . BSTS possesses low energy optical phonons which strongly couple with the heat carrying acoustic phonons leading to ultra‐low κ lat . Further, Cl has been doped at the S site of BSTS which increases the electron concentration and reduces the κ lat resulting in a promising n‐type thermoelectric figure of merit (zT) of ≈0.6 at 573 K. Abstract : Low lattice thermal conductivity and high electron mobility provide promising thermoelectric performance in a 3D topological insulator, Bi1.1 Sb0.9 Te2 S. The low thermal conductivity originates from the strong anharmonicity, while the high carrier mobility results from metallic suface states in the topological insulator.